Enhancing Solid Fuel Properties of Sawdust Torrefaction using a Rotary Drum Reactor - Sripha, Yutthana; Phengpom, Tinnapob; Kaewpengkrow, Prangtip Rittichote; Thianpong, Chinaruk (My University, 2026)
This study investigated the physicochemical properties of torrefied sawdust obtained from the industry using a rotary drum reactor. Sawdust samples were torrefied at 220, 250, and 280 °C for 15, 30, and 45 min under a nitrogen atmosphere. Proximate analysis was conducted to determine the moisture, volatile, fixed carbon, and ash contents. The volatile content of the torrefied sawdust ranged from 69.05 to 88.06 wt.%. The results suggested that the chemical energies of solid fuels are stored in volatile matter and fixed carbon, both of which have a higher reactivity during carbonization. Characterization of functional groups was conducted using an FTIR spectrophotometer, and the higher heating value (HHV) of the torrefied sawdust was also investigated. The HHV increased from 15.36 MJ/kg to 21.13 MJ/kg, with the highest HHV achieved at 280°C for 45 min. Moreover, the torrefaction at 250 °C for 30 min gave a biofuel with more than 80% energy density, which allowed us to classify this biofuel as lignite. Therefore, torrefaction is a promising pretreatment technique that can improve the energy quality and combustion properties.
Keywords: biomass; sawdust; torrefaction; wood waste